Charismatic leadership and tacit knowledge sharing in the context of enterprise systems learning: the mediating effect of psychological safety climate and intrinsic motivation. Issue 2 (1st February 2017) - Shao, Zhen; Feng, Yuqiang; Wang, Tienan
ABSTRACT: Drawing upon charismatic leadership and intrinsic motivation theory, we developed a theoretical model to examine the impact mechanism of leader charisma on individuals' tacit knowledge-sharing behaviour in the context of an Enterprise Systems learning team. We conducted a survey-based field study to examine the theoretical model and hypotheses. A total of 153 questionnaires were distributed to employees from more than 20 branches of the Beidahuang Group in China and 117 valid questionnaires were returned. Results from partial least squares analysis suggest that leader charisma has a strong influence on psychological safety climate, which in turn has a positive impact on individuals' intrinsic motivation and their tacit knowledge-sharing behaviour. Our research findings unpack the impact mechanism of charismatic leadership on tacit knowledge sharing, and provide guidelines for the team leader to exhibit charismatic leadership traits in order to promote a psychological safety climate and facilitate an effective knowledge sharing of enterprise systems.